Burial history and thermal maturity of the atypical petroleum system of the Paraná Basin (Irati and Ponta Grossa formations), Brazil. (December 2022) - Martins, Cintia Mayra S.; Cerqueira, José Roberto; Celino, Joil José; Ribeiro, Hélio Jorge P. Severiano; Garcia, Karina S.; de Oliveira, Olívia Maria C.; Queiroz, Antônio Fernando de S.
Abstract: The main characteristic of the intracratonic sedimentary Paraná Basin, southern Brazil, is the atypical hydrocarbon generation through the heat from basic intrusive rocks. Potential hydrocarbon source shales from the Irati and Ponta Grossa formations were identified and characterised via stratigraphic data, total organic carbon (TOC - LECO ) analyses and pyrolysis ( Rock-Eval 6 ) of well samples. Geochemical analyses showed that in wells under study, the Irati Formation has organically rich shales, and the Ponta Grossa Formation has low potential for hydrocarbon generation. 1D generation modelling using 16-well 1D and PetroMod® software was developed aiming to establish the thermal and subsidence history in the area and to determine hydrocarbon generation and expulsion. Geochemical data from the wells was used, and information on sedimentology and stratigraphy was obtained from the literature. Thermal history was calibrated using values of vitrinite reflectance, Tmax and downhole temperature, and the geothermal gradient used in the models was 28–42 °C/km. The relative erosive thicknesses of the stratigraphic units were estimated. The results showed that in regions without igneous intrusions, the Irati shales are immature for hydrocarbon generation and do not have an organic matter transformation rate, which is consistent with the results of Rock-Eval pyrolysis and %Ro. However, in wells containing igneous intrusive rocks in the Irati shales, the transformation rates varied according to the thickness and number of intrusions, reaching 100% organic matter transformation; due to its quality (Type I kerogen), this rate is favourable for oil and gas generation. The Ponta Grossa source rock showed thermal maturation by subsidence corresponding to the oil generation window, with higher maturation anomalies near igneous intrusions. The organic matter transformation rate reached 70% in the absence of igneous intrusions and nearly 100% in the presence of igneous intrusions. Despite having good maturity, the characteristics regarding the quantity and quality of organic matter suggest a moderate potential for gas generation in the Ponta Grossa Formation in the study area. The depositional history model showed that the highest subsidence rate occurred during the Early Cretaceous and was related to the burial associated with the basalt thickness of the Serra Geral Formation. Highlights: This study combines organic geochemistry and petroleum generation modelling. Igneous intrusions had an important impact on the generation of hydrocarbons. Simulation 1D of petroleum generation without and with the igneous sill complex. Modelling showed that Ponta Grossa Formation attained the oil window by burial.